Catholicism : the story of Catholic Christianity - O'Collins, Gerald; Farrugia, Mario (Oxford ; New York : Oxford University Press, 2003)
How did Roman Catholicism and its beliefs and practices come to be what they are? This lively and readable account provides an up-to-date introduction, explaining what is distinctively Catholic. The authors move through history to sum up the present characteristics of Catholic Christianity and the major tests it faces in the third millennium. Explaining matters in a fresh and original way, they do justice to the Catholic heritage and show that Catholicism is a dynamic and living faith. Well-structured, highly informative, and clearly written, the book does not duck critical issues--such as the ministry of women and dialogue with other religions--or the negative side of history. Rather, O'Collins and Farrugia explore challenges facing Catholics and other Christians and engage with contemporary moral issues. This is an authoritative and accessible introduction to Catholicism for the modern reader.
1. The first thousand years -- 2. The second thousand years -- 3. Revelation, tradition, and scripture -- 4. The Tripersonal God and the Incarnate Son -- 5. The human condition: created and sinful -- 6. The life of grace and the hope of glory -- 7. The sacraments -- 8. The Catholic Church and its mission -- 9. Catholic moral life and teaching -- 10. Basic characteristics of Catholicism -- 11. Current challenges.
Cf. OCLC #52485809 with which this volume seems to be identical except for the addition of a bibliography and an index.
Includes bibliographical references (p. 394-396) and index.
Keywords: Catholic Church -- Doctrines; Catholic Church -- Doctrines -- History